Job characteristics and job performance among professional nurses in the university hospitals of people's Republic of China - Yuxiu,P. (Chiang Mai University, 2015)
This descriptive correlational study aimed to describe the level of job characteristics and job performance and to examine the relationship between job characteristics and job performance among professional nurses in two randomly- selected university hospitals in China. Data were collected from 328 professional nurses from a total population of 1,672, using stratified random sampling. Research instrument was composed of three parts: Demographic Data Form, Job Diagnostic Survey (JDS) and the Six-Dimension Scale of Nursing Performance (Six-D Scale). Reliabilities of the JDS and the Six-D Scale were.86 and.96, respectively. Descriptive statistics and Pearson's product moment were used for data analysis. Findings showed that: 1) the level of overall job characteristics as perceived by professional nurses was at a moderate level. Among the seven dimensions of job characteristics, the level of job characteristics for dealing with others, task significance, feedback from agents and feedback from job itself were at a high level. The other dimensions, i.e., task identity, skill variety and autonomy were at a moderate level; 2) The quality of job performance in each dimension and overall job performance were at a moderate level and; 3) Among the subjects, a significant relationship was found between job characteristics and job performance that was at a moderate level (r=.36, p<.01). The results of this study can be used in planning work and training programs for professional nurses to ensure high level of job performance.